2007
DOI: 10.1007/s10812-007-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bridging aza-substitution on electronic structure and spectral-luminescent properties of isobacteriochlorin NH-isomers

Abstract: UDC 535.37We have investigated the spectral characteristics, quantum yield ϕ F , lifetime τ F , and polarization of fluorescence of NH-isomers of dibenzobarrelene disubstituted tetraazaisobacteriochlorin at 293 and 77 K. The following information has been obtained from low-temperature measurements: 1) the weak shoulder on the edge of the long-wavelength 0-0 absorption band disappears at 77 K and, therefore, can be assigned to the cis-NH-isomer [the principal component of the tautomeric mixture is the trans-iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Combination of these factors deserves consideration as a method for creating compounds with controlled properties. Spectral and luminescence characteristics of hydrogenated tetraazaporphine derivatives (also called porphyrazine) have been well studied [1][2][3][4][5][6][7][8].Studies showed that hydrogenation of one or two opposed pyrrole rings in tetraazaporphine (H 2 TAP) causes significant fluorescence quenching [1,3,5,8]. This quenching may be due to an increase of the probabilities for the two radiationless intramolecular processes of intersystem crossing S 1 ‫ב‬ T 1 , k ST , and internal conversion S 1 ‫ב‬ S 0 , i.e., energy exchange of the S 1 electronic state onto vibrations of the molecule in the ground state S 0 , the probability of which increases with lowering of the S 1 level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of these factors deserves consideration as a method for creating compounds with controlled properties. Spectral and luminescence characteristics of hydrogenated tetraazaporphine derivatives (also called porphyrazine) have been well studied [1][2][3][4][5][6][7][8].Studies showed that hydrogenation of one or two opposed pyrrole rings in tetraazaporphine (H 2 TAP) causes significant fluorescence quenching [1,3,5,8]. This quenching may be due to an increase of the probabilities for the two radiationless intramolecular processes of intersystem crossing S 1 ‫ב‬ T 1 , k ST , and internal conversion S 1 ‫ב‬ S 0 , i.e., energy exchange of the S 1 electronic state onto vibrations of the molecule in the ground state S 0 , the probability of which increases with lowering of the S 1 level.…”
mentioning
confidence: 99%
“…Combination of these factors deserves consideration as a method for creating compounds with controlled properties. Spectral and luminescence characteristics of hydrogenated tetraazaporphine derivatives (also called porphyrazine) have been well studied [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…This proves that the assignment of the Q 2 (0-0) band is correct (see above and Table 1). Note two points: First of all, we see a similarity to the free base H 2 TAiBC tt , the NH isomer a, for which the Q 2 (0-0) band also undergoes a short-wavelength shift at 77 K [6]. Such sensitivity of the spectral bands to the effect of external factors (the properties of the medium also change on freezing down to 77 K) is not typical for porphyrins.…”
mentioning
confidence: 67%
“…The combination of the two indicated structural factors can make it possible to control the physicochemical properties of molecular systems based on porphyrazines. A theoretical study of molecules with hydrogenated pyrrole rings and aza bridges should facilitate a deeper understanding of the electronic structure and physicochemical properties of molecules of this type.Recently a number of papers have been published on study of the photophysics of porphyrazine molecules with hydrogenated pyrrole rings [2][3][4][5][6][7][8][9]. However, mainly free bases have been studied, and only in [2] were some of the objects of investigation a zinc complex of substituted dihydroporphyrazine (tetraazachlorin).…”
mentioning
confidence: 99%
See 1 more Smart Citation